RTHP-16. RADIATION INDUCED SIGNAL CHANGES ON MAGNETIC RESONANCE IMAGING IN ADULT PATIENTS WITH BRAIN TUMORS TREATED WITH PENCIL BEAM SCANNING PROTON THERAPY. (5th November 2018) - Rongthong, Warissara; Laack, Nadia; Beltran, Chris; Chan Tseung, Hok seum Wan; Roberts, Kristofer; Vora, Sujay; Mahajan, Anita
Abstract: OBJECTIVES: We report radiation induced signal changes (RIC) on MRI in adult patients with brain tumors treated with pencil beam scanning proton therapy (PBS-PRT). METHODS: All patients > 18 years receiving standard fractionation RT (4554 GyE) for a primary brain tumor with > 6 month follow-up were included. Post-RT MRIs were compared to the pre-RT scans. RIC was defined as new contrast enhancement (CET1W) and/or T2-FLAIR (T2W) changes MRI outside the GTV (CTCAE v4.0 grading was used). Monte Carlo, RBE (relative biologic effectiveness), and LET plan evaluation pre-RT were performed. Tumor, clinical and treatment factors were analyzed. RESULTS: Twenty-one patients were identified. RIC developed in 17/21 (81%: 2 CET1W, 15 T2W). All RIC appeared adjacent to surgical cavity and/or GTV in areas of increased RBE. 3 patients developed symptomatic RIC: All three patients had CET1W changes within tumor. Patient 1 received 50.4 GyE for a subtotally resected skull base meningioma. T2W changes developed at 3 months and CET1W changes in the tumor appeared at 7 months. Grade 2 symptoms (headache, unsteadiness, incontinence) developed by 14 months. Symptoms and imaging improved with dexamethasone taper by 22 months. Patient 2 received 54GyE for a subtotally resected grade II oligoastrocytoma. 4 months post-RT patient developed perilesional T2W. Headaches developed at 7 months and resolved following dexamethasone taper. Patient 3 received 54GyE for a progressive tectal plate glioma. At 2 months post-RT, CET1W changes within the tumor and T2W perilesional changes developed. Grade 3 diplopia developed a month later. The CET1W and T2W changes resolved at 13 months. No relationships between factors and RIC were identified. CONCLUSION: Asymptomatic RIC are common after RT, but symptoms are infrequent. Symptoms appear to be associated with post-PRT changes within tumor. A larger cohort including comparison to photon treatments and RBE will be evaluated in the future.